2015
DOI: 10.1002/gps.4289
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristic of patients presenting with lacunar stroke and cerebral small vessel disease may predict future development of depression

Abstract: Baseline functional status and severity of WMH and development of cognitive decline predict the occurence of late-onset depression in patients with SVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 74 publications
(134 reference statements)
1
31
0
2
Order By: Relevance
“…Microbleeds were associated with LLD but not with EOD [146]; these lesions and WMHs were associated with cerebral small vessel disease (CSVD) and reduced cerebral blood flow [148], which predicted depressive disorder in healthy older adults [149]. Depressive symptoms were seen in 10.1–39.8 % of patients with CSVD [2, 150], and patients with silent cerebral infarcts and chronic heart failure had an increased prevalence of MDD compared to those without chronic heart failure [151]; further, minor cerebrovascular incidents predisposed patients to LLD/VaDep [152]. Lacunar infarcts in deep white matter were associated with greater psychomotor retardation, motivation and energy loss, depressed mood, and cognitive decline, presumably due to disruption of frontal–subcortical networks [153, 154], while others suggested that apathy, but not depression in CSVD, is related to damage in circuits associated with emotion regulation [155].…”
Section: Resultsmentioning
confidence: 99%
“…Microbleeds were associated with LLD but not with EOD [146]; these lesions and WMHs were associated with cerebral small vessel disease (CSVD) and reduced cerebral blood flow [148], which predicted depressive disorder in healthy older adults [149]. Depressive symptoms were seen in 10.1–39.8 % of patients with CSVD [2, 150], and patients with silent cerebral infarcts and chronic heart failure had an increased prevalence of MDD compared to those without chronic heart failure [151]; further, minor cerebrovascular incidents predisposed patients to LLD/VaDep [152]. Lacunar infarcts in deep white matter were associated with greater psychomotor retardation, motivation and energy loss, depressed mood, and cognitive decline, presumably due to disruption of frontal–subcortical networks [153, 154], while others suggested that apathy, but not depression in CSVD, is related to damage in circuits associated with emotion regulation [155].…”
Section: Resultsmentioning
confidence: 99%
“…In both VaD and DM2, the amount of tracer trapped in the brain parenchyma is positively correlated with cognitive deficits in several behavioral tests in rats(30, 34). This would be of interest to WML as these are also associated to cognitive performance(117). Is it possible that glymphatic clearance failure is correlated with WML burden?…”
Section: Altered Glymphatic Function In Svd?mentioning
confidence: 99%
“…Underlying vascular pathologies are arteriolosclerosis, lipohyalinosis, fibroid necrosis, oedema and damage to the blood-cerebrospinal fluid and blood–brain barriers (BCB/BBB), the latter resulting in chronic leakage of fluid and macromolecules in the white matter and inflammation (reviewed by Kalaria, 2016) [5]. Although SSVD pathogenesis remains poorly understood, it is an age-related condition, associated with a number of risk factors including systemic hypertension [69], chronic kidney disease [10, 11], smoking [12], metabolic syndrome [8, 13, 14], osteoporosis [15], chronic obstructive pulmonary disease [16] and sleep-apnoea syndrome [17]. The SSVD clinical manifestations are largely due to complete (lacunes) or incomplete (WML) infarction(s) and microbleeds resulting in cognitive, motor and mood disturbances and eventually functional disability [2], although same lesions might appear in cognitively intact persons during normal ageing.…”
Section: Methodsmentioning
confidence: 99%